Macroprudential policies at work: How do government-owned banks affect credit markets? - Paulo Capeleti; Márcio Gomes Pinto Garcia; Fábio Miessi Sanches (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2018)
How countercyclical macroprudential credit policies affect the loan spread? To answer this question, we propose a microeconomic model of bank competition that contemplates differences in the behavior of public and private banks and the peculiarities of the market for corporate loans vis-a-vis the market for consumer loans. We solve the model and calibrate it using parameters of the Brazilian economy, where government-owned banks not only account for almost half of the outstanding loans in the credit market but also have played a strong countercyclical role in the economy. Subsequently, we use the equilibrium conditions of the model to study the effects of macroprudential credit policies on loan spreads. The results indicate that credit expansion by public banks is more effective to reduce loans interest rates during recession periods than during periods of economic expansion.
Keywords: E13; E43; E51; 330; Interest Rate Spread; Bank Competition; Public and Private Loans